Potential trends in invasion risk of the yellow-legged hornet, Vespa velutina, in Ukraine - Tytar, V.M.; Kozynenko, I.I. (Доповіді НАН України, 2023)
In the recent decade an alarming problem has risen about the invasion of Vespa velutina Lepeletier, 1836 (Hymenoptera: Vespidae) in European ecosystems. The species can cause serious damage to ecosystem biodiversity and in areas where it has been introduced, and can have serious impacts over beekeeping. Bioclimatic modelling suggests that under current climate conditions representatives of the invasive species have chances in the near term to invade a number of regions in Ukraine, especially in the west of the country, including Transcarpathia, and Crimea. Under predicted climate change the hornet will most likely extend its presence in Ukraine.